Development and characterization of sorafenib-loaded lipid nanocapsules for the treatment of glioblastoma. (1st January 2018) - Clavreul, Anne; Roger, Emilie; Pourbaghi-Masouleh, Milad; Lemaire, Laurent; Tétaud, Clément; Menei, Philippe
Abstract: Anticancer agents that target both tumor cells and angiogenesis are of potential interest for glioblastoma (GB) therapy. One such agent is sorafenib (SFN), a tyrosine kinase inhibitor. However, poor aqueous solubility and undesirable side effects limit its clinical application, including local treatment. We encapsulated SFN in lipid nanocapsules (LNCs) to overcome these drawbacks. LNCs are nanocarriers formulated according to a solvent-free process, using only components that have received regulatory approval. SFN-LNCs had a diameter of 54 ± 1 nm, high encapsulation efficiency (>90%), and a drug payload of 2.11 ± 0.03 mg/g of LNC dispersion. They inhibited in vitro angiogenesis and decreased human U87MG GB cell viability similarly to free SFN. In vivo studies showed that the intratumoral administration of SFN-LNCs or free SFN in nude mice bearing an orthotopic U87MG human GB xenograft decreased the proportion of proliferating cells in the tumor relative to control groups. SFN-LNCs were more effective than free SFN for inducing early tumor vascular normalization, characterized by increases in tumor blood flow and decreases in tumor vessel area. These results highlight the potential of LNCs as delivery systems for SFN. The vascular normalization induced by SFN-LNCs could be used to improve the efficacy of chemotherapy or radiotherapy for treating GB.